Beat and metaphoric gestures are differentially associated with regional cerebellar and cortical volumes. Issue 10 (14th July 2015) - Bernard, Jessica A.; B. Millman, Zachary; Mittal, Vijay A.
Abstract Gestures represent an integral aspect of interpersonal communication, and they are closely linked with language and thought. Brain regions for language processing overlap with those for gesture processing. Two types of gesticulation, beat gestures and metaphoric gestures are particularly important for understanding the taxonomy of co‐speech gestures. Here, we investigated gesture production during taped interviews with respect to regional brain volume. First, we were interested in whether beat gesture production is associated with similar regions as metaphoric gesture. Second, we investigated whether cortical regions associated with metaphoric gesture processing are linked to gesture production based on correlations with brain volumes. We found that beat gestures are uniquely related to regional volume in cerebellar regions previously implicated in discrete motor timing. We suggest that these gestures may be an artifact of the timing processes of the cerebellum that are important for the timing of vocalizations. Second, our findings indicate that brain volumes in regions of the left hemisphere previously implicated in metaphoric gesture processing are positively correlated with metaphoric gesture production. Together, this novel work extends our understanding of left hemisphere regions associated with gesture to indicate their importance in gesture production, and also suggests that beat gestures may be especially unique. This provides important insight into the taxonomy of co‐speech gestures, and also further insight into the general role of the cerebellum in language. Hum Brain Mapp 36:4016–4030, 2015. © 2015 Wiley Periodicals, Inc.